THE FORMS OF ADDRESS OF THE SASAK COMMUNITY IN USING SASAK SPEECH LEVELS IN KERUAK COMMUNITY - ABDUL MAJID JUNAIDI (LPPM Universitas Gunung Rinjani, 2020)
This research is intended to describe the types of Sasak speech levels, the phonological,morphological, and lexical variations, and the contexts that determine the usage of eachtype of Sasak speech levels. There are three steps applied in this research; datacollecting, data analysis, and result presentation. The data are taken through in-depthinterview method by employing recording and note-taking techniques. The data are alsogathered from some literary sources as well as the writer’s insight and understanding as anative speaker of Sasak people in Keruak Community.The results of this research indicatethat there are three types of Sasak speech levels, namely, bahasa Sasak Jamaq(intimate/ordinary), bahasa Sasak Alus Madya (medium/moderate), and bahasa SasakAlus Utama (high). Several factors are addressed to have affected the unfavorable use ofSasak speech levels among the youths. First, there is the environment factor, which is notconducive enough to allow people to use to hearing and practicing the honorific Sasaklexicon. This is due to the assumption that Speech levels belong only to the bangsawanaristocrat family members. Second, the numbers of the noblemen family members whouse this variety are also decreasing. Third, the widely use of Bahasa Indonesia in almostevery domain of language use cannot be avoided to influence the young generation tocommunicate in it wherever possible. And fourth, it appears that the time allotment to theteaching of Sasak as local content in the school curriculum does not allow covering theteaching of the speech level.Key Words: Address, Sasak Language, Sasak Speech Levels.Penelitian ini dimaksudkan untuk menggambarkan; jenis tingkat tindak tutur, aspekfonologi, morfologi, dan variasi leksikal tindak tutur bahasa Sasak, dan konteks yangmenentukan penggunaan setiap jenis tingkat tutur Sasak. Ada tiga langkah strategis yangditerapkan dalam penelitian ini, yaitu, pengumpulan data, analisis data, dan presentasianalisis data. Data yang diambil melalui metode wawancara dengan merekam danmencatat. Data juga dikumpulkan dari beberapa sumber sastra, wawasan penulis, danpemahaman sebagai pembicara asli orang Sasak di desa Keruak. Penelitian inimenunjukkan bahwa ada tiga jenis tingkat tutur bahasa Sasak yaitu bahasa Sasak Jamaq,Alus Madya (sedang), dan Alus Utama (tinggi). Beberapa faktor yang ditujukanmempengaruhi penggunaan bahasa Sasak di antara pemuda. Pertama, faktor lingkunganyang tidak kondusif untuk memungkinkan orang untuk menggunakan leksikon Sasak. Halini disebabkan asumsi bahwa tingkat tindak tutur hanya milik para bangsawan. Kedua,jumlah anggota keluarga bangsawan yang menggunakan varietas ini juga menurun.Ketiga, banyak penggunaan Bahasa Indonesia di hampir setiap domain penggunaanbahasa tidak bisa dihindari untuk mempengaruhi generasi muda untuk berkomunikasidimanapun. Dan keempat, tampaknya saat penjatahan pada ajaran Sasak sebagai kontenlokal dalam kurikulum sekolah tidak diimplementasikan.Keywords: Nama Panggilan, Bahasa Sasak, Tingkat Tindak Tutur